AG versus Copeland Over Patent Rights: Pan War - Douglas, Sean (Newsday)
Attorney General Anand Ramlogan alleged that engineer, Professor Brian Copeland's firm, Panadigm Innovations Limited, was making and selling special steelpans to which the Government owns the patent. Copeland was awarded the nation's highest honour, the Order of Trinidad and Tobago, for his work on developing the G-pan. Ramlogan stated that while Copeland had been made to assign the patent for the G-pan to the Government, he had made and sold G-pans without Government's permission. Ramlogan also said there is the substantive claim against Copeland related to another steelpan invention, the Percussive Harmonic Instrument (PHI) or electronic pan.
Keywords: Inventors -- Trinidad and Tobago; Steel bands (Music) -- Trinidad and Tobago; Steel band music -- Trinidad and Tobago; Steel drum (Musical instrument) -- Trinidad and Tobago